Professions, entrepreneurs, employees and the new German tax (cut) reform 2000: A MICSIM microsimulation analysis of distributional impacts - Joachim Merz; Henning Stolze; Markus Zwick (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2002)
With the tax reform 2000 Germany has seen the implementation of the most ambitious tax reduction programme in its post-war history. In the period from 1998 to 2005, taxpayers will benefit substantially from net tax relief more than DM 100 billions in total. It is expected, that private consumption and investment are stimulated - two essential requirements for promoting growth and employment. Under the aspect of the tax reform 2000 and the Karlsruher Entwurf (an expert draft on further income tax reform approaches) compared to the former taxbase system we investigate in our paper overall and distributional and redistributional impacts on the self employed (professions (free lancers) and entrepreneurs) and employees besides other socioeconomic grouping like gender and family type. In addition, a decomposition analysis based on a generalized entropy approach quantifies the socioeconomic subgroups' inequality contribution to overall inequality. Together with the recent poverty and wealth report for our government, this is the first time that the anonymized microdata records of the German Income Tax Statistic can be used by researchers within the Federal Statistical Office. Such a microdata file is essential for analysing above all the often neglected situation of the self-employed; in traditional surveys, where, in principle, firm information yielding the final income and taxes to be paid are not available for the self-employed. – – Mit der Steuerreform 2000 wurde das ambitionierteste Steuerreduktionsvorhaben in der deutschen Nachkriegsgeschichte beschlossen. In den Jahren von 1998 bis 2005 werden Steuerzahler von einer Nettoentlastung von insgesamt mehr als 100 Mrd. DM profitieren. Man erwartet hierdurch eine Stimulation der privaten Ausgaben sowie der Investitionen, zwei wichtige Voraussetzungen für Wirtschaftswachstum und mehr Beschäftigung.Auf der Grundlage von Vergleichen zwischen dem früheren Steuersystem mit der Steuerreform von 2000 und dem Karlsruher Entwurf (einem Vorschlag einer Expertengruppe für weitere Einkommenssteuerreformen) werden in diesem Paper Verteilungs- und Umverteilungseffekte auf die Gruppe der Selbständigen (Freie Berufe und Unternehmer) und anderen sozioökonomischen Gruppen (z.B. unterschieden nach Geschlecht, Familientypus etc.) untersucht. Zusätzlich wird die Ungleichheitsverteilung einzelner sozioökonomischer Untergruppen im Vergleich zur gesamten Ungleichheit mit Hilfe einer Dekompositionsanalyse auf der Basis der Informationstheorie untersucht.Neben dem kürzlich erschienenen Armuts- und Reichtumsbericht der Bundesregierung ist dies das erste Mal, dass anonymisierte Mikrodatenfiles der deutschen Einkommenssteuerstatistik der Wissenschaft innerhalb des Statistischen Bundesamtes zur Verfügung gestellt werden. Solche Mikrodaten sind jedoch für die Analyse der oft vernachlässigten Selbständigen unerlässlich; über konventionellen Umfragen sind präzise Daten über das Einkommen und die Steuerlast der Selbständigen praktisch nicht zu erheben.
Keywords: D30; D31; J23; 330; microsimulation; German tax reform; Karlsruhe proposal; self-employed; professions; entrepreneurs; employees; distributional and redistributional policy impacts; inequality and decomposition of inequality; Mikrosimulation; Einkommessteuerreform; Karlsruher Entwurf; Selbständige; Freie Berufe; Unternehmer; Angestellte; Verteilungs- und Umverteilungseffekte; Ungleichheit und Dekomposition von Ungleichheit; Einkommensteuer; Steuerreform; Simulation; Entrepreneurship-Ansatz; Selbstständige; Angestellte; Deutschland; Verteilungswirkung